2017
DOI: 10.1007/s10266-017-0299-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bite openings and mandibular protrusion on genioglossus muscle activity in healthy adults with oral appliance

Abstract: Oral appliance (OA) can effectively treat obstructive sleep apnea; however, numerous types of oral appliances and designs are variable and the precise mechanisms behind differences in treatment outcomes are uncertain. The objective of this study was to evaluate the effects of different degrees of mandibular position [4° of bite openings (BO): 2, 4, 8 and 12 mm; and protrusion (P): 0, 50%, MAX], for both the upright and supine positions: BOP, BOP, BOP, BOP, BOP, BOP; with an OA on the: (1) activity of the genio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The design of the MAD has a major influence on its success rate on the patient [12], and the design features have an influence on efficacy, tolerance, and compliance [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…The design of the MAD has a major influence on its success rate on the patient [12], and the design features have an influence on efficacy, tolerance, and compliance [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that OSAS is more effectively treated with an increased BO; however, a minimal BO is more comfortable for the subject [6, 22]. Long et al [13] reported that an increase in BO of 2–12 mm and even maximum mandibular protrusion may not negatively affect the temporomandibular joint. Therefore, in addition to mandibular protrusion, considering adjustment of the BO in OAs might minimize discomfort in patients with OSAS who are using OAs.…”
Section: Discussionmentioning
confidence: 99%
“…1). The position of the GG was confirmed as previously described to enable the monitoring of GG activity during respiration [13]. In this study, because we assumed that respiratory-related GG muscle activity is symmetric in normal subjects, we recorded only left GG muscle activity.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations